How and when does responsible leadership affect employees’ pro-environmental behavior? - Zhou, Yuanyuan; Ning, Yumei; He, Hui; Li, Dan (Frontiers in Psychology, 2022)
By integrating the resource accumulation perspective and the Job Demands-Resources (JD-R) model, this research explores the impact mechanism of responsible leadership on employees’ pro-environmental behaviors (EPB). We conducted a survey to collect data from 319 employees in Chinese companies in three waves. Our research found that responsible leadership had significantly positive effect on EPB; employees’ perceived organizational support toward the environment (POS-E) and green self-efficacy played a serial multiple mediating role; meanwhile, employees’ chronic regulatory focus moderated the relationship between responsible leadership and EPB, with promotion focus strengthening the relationship and prevention focus weakening the relationship. Our findings support the applicability of JD-R model in the field of EPB, enrich the theoretical research on responsible leadership and EPB, and also provide a practical basis for organizations to effectively stimulate EPB and promote sustainable development.